L’innovation au pluriel des cré-acteurs alpins - Andréa Finger-Stich (Revue de Géographie Alpine)
The capacity to innovate for a sustainable development of alpine territories cannot depend only on economic, legal and political conditions defined by the State at national and international levels. It depends also on local conditions that situate historically and geographically the actors in a continuity of social and ecological relationships. This approach highlights the collective - thus organisational - dimensions of the innovation process, including the imagination, the development, the implementation and even the diffusion of a new practice. Our point of view is that for contributing to the sustainable development of the Alps, innovations need to change the ecological, political, social and cultural relationships engaging the actors in these territories. This change affects as much the object territory as the subject actor of the territory. This is why innovating in the Alps means also innovating the Alps and the alpine actors (Cosalp, 2008). Based on a research about local people’s participation in the management of alpine communal forests, the article shows the importance of local interactions involving actors of diverse occupation, gender, age and origins.